FACTOR CONTRIBUTING TO INTERNET ADDICTION AND ITS INFLUENCE ON ACADEMIC PROCRASTINATION BEHAVIOR AMONG UUM STUDENTS (Journal of Governance and Development (JGD), 2021)
has led to the existence of an internet dependence dilemma (internet addiction) which leads to their low efficiency, lack of interest andmotivation, postponing important academic tasks and jobs, and causing academic delays. This study was conducted to investigatethe relationship of between particular factors contributing to internet addiction namely anxiety, depression, self-control and internetaddiction itself with academic procrastination among undergraduate students from UUM College of Business (COB). This study is included 370 UUM COB undergraduate students by using questionnaire to collect data and data analysis is conducted using Statistical Package for Social Sciences (SPSS) software. Descriptive analysis, reliability test, normality test, Pearson correlation analysis and multiple regression analysis were conducted to identifying relationship between independent variables and dependent variable. Results showed anxiety was found a significant relationship with academic procrastination. Besides that, depression and internet addiction were also significant contributing factor to academic procrastination. Lastly, existence of negative significant relationship between self-control and academic procrastination.